2015
DOI: 10.1016/j.bbamcr.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Selective killing of G2 decatenation checkpoint defective colon cancer cells by catalytic topoisomerase II inhibitor

Abstract: Cancer cells with defective DNA decatenation checkpoint can be selectively targeted by the catalytic inhibitors of DNA topoisomerase IIα (topo IIα) enzyme. Upon treatment with catalytic topo IIα inhibitors, cells with defective decatenation checkpoint fail to arrest their cell cycle in G2 phase and enter into M phase with catenated and under-condensed chromosomes resulting into impaired mitosis and eventually cell death. In the present work we analyzed decatenation checkpoint in five different colon cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…For larger investigations, for example, EU-initiated toxicological investigations, IC 50 protocols are, therefore, strictly standardized to allow comparisons of toxicity (67). The QPI-generated proliferation curves in this study corresponded well with other studies showing the effect of etoposide (33,37,(40)(41)(42). Etoposide has previously been shown to have IC 50 values from 0.1 mM to over 200 mM.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…For larger investigations, for example, EU-initiated toxicological investigations, IC 50 protocols are, therefore, strictly standardized to allow comparisons of toxicity (67). The QPI-generated proliferation curves in this study corresponded well with other studies showing the effect of etoposide (33,37,(40)(41)(42). Etoposide has previously been shown to have IC 50 values from 0.1 mM to over 200 mM.…”
Section: Discussionsupporting
confidence: 79%
“…For adequate and easy assessment of cell proliferation, a userfriendly method, that nondestructively assesses cell proliferation by direct cell count in standard multiwell plates, would be preferred. We compared cell growth and IC 50 data with previously reported studies (40)(41)(42). We used the QPI technique digital holographic microscopy (DHM), which has been shown to be well suited for this kind of studies (29,32,34,38).…”
Section: Introductionmentioning
confidence: 99%
“…37, 4951 Two reports have also demonstrated that decatenation G 2 checkpoint-defective melanoma and colon cancer cell lines are hypersensitive to PI3-kinase inhibitors and topo II catalytic inhibitors, respectively. 51, 52 Because the decatenation G 2 checkpoint response is molecularly distinct from the DNA damage G 2 checkpoint and the SAC, 1, 16, 17 and the gene expression signature of decatenation G 2 checkpoint function identified in this study is associated with OS outcomes in breast cancer patients (Fig. 5, Table S6), it may be feasible to induce synthetic lethality in tumors exhibiting defects in decatenation G 2 checkpoint function with pharmacological agents that catalytically inhibit topo II activity, providing an alternative strategy for targeted drug design to treat poor prognosis LumB breast cancers and a subset of LumA breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…All the synthesized cyclam fused naphthalimide derivatives were verified by 1 H NMR, 13 C NMR and HRMS, while the metal complexes were verified by HRMS and HPLC. 1 H NMR and 13 C NMR measured on a Bruker AV-400 spectrometer (in CDCl 3 and DMSO-d 6 , TMS as an internal standard).…”
Section: Methodsmentioning
confidence: 99%
“…New research also found that topo II were promising therapeutic target for the treatment of colon cancers with defective decatenation checkpoint. 13 However, it is found that selective topo I inhibition can induce a concomitant rise in the level of topo II expression, and vice versa. This phenomenon would lead to drug resistance and failure of clinical therapies ultimately.…”
Section: Introductionmentioning
confidence: 98%